Age-dependent sex ratios of motor neuron disease: French nationwide study and meta-analysis. (1st May 2018) - Ahmadzai, Pasarlai; Kab, Sofiane; Vlaar, Tim; Artaud, Fanny; Carcaillon-Bentata, Laure; Canonico, Marianne; Moisan, Frédéric; Elbaz, Alexis
Abstract : Objective: To examine the relation of age with male-to-female (M/F) ratios and incidence rates of motor neuron disease (MND) in a French nationwide study and meta-analysis of incidence studies. Methods: We used data from the French National Health Insurance databases. Patients with incident MND (2010–2014) were identified based on drug claims (riluzole), hospitalization records, death records, and long-term chronic disease benefits. We estimated age-specific M/F incidence ratios using Poisson regression. Poisson, Gompertz, and multistep models were used to model the relation between age and incidence. We performed a meta-analysis (n = 28 studies) and used meta-regression to examine the relation of age with incidence rates and ratios. Results: In France, we identified 10, 848 patients with incident MND (6, 021 men, 4, 827 women). Incidence was higher in men than in women in all age groups. M/F ratios were significantly different across age groups and followed a quadratic trend ( p < 0.001). Between 20 and 49 years, the average M/F ratio was 2.26 (95% confidence interval [CI] = 1.96–2.62); it was 1.41 (95% CI = 1.35–1.47) between 50 and 84 years, and 1.88 (95% CI = 1.64–2.17) after 85 years. Incidence was lower in women than men at younger ages, but increased more steeply in women than men. Similar patterns were observed in the meta-analysis of incidence studies, especially in 19 higher-quality studies. Conclusion: The relation between age and M/F incidence ratios of MND follows a quadratic U-shaped pattern with an abrupt drop after the fifth decade. The change in M/F ratios before and after menopause suggests that reproductive/hormonal protective factors have a role in women and should prompt further studies to explore this hypothesis.